Study of gas hydrate formation and wall deposition under multiphase flow conditions - Straume, Erlend Oddvin (2017)
Potential flow assurance problems in oil and gas pipelines related to gas hydrates have traditionally been resolved by implementing hydrate avoidance strategies, such as water removal, insulation, and injection of thermodynamic inhibitors. As a means of lowering development and operational costs in the industry, hydrate management is becoming a more viable approach. “Hydrate Management” strategies differ from standard “Hydrate Avoidance” in the fact that, instead of focusing on preventing hydrate formation, these strategies focus on minimizing the risk of plugging and ensuring flow using methods that allow transportability of hydrate slurries with the hydrocarbon production fluids in multiphase flow conditions where hydrates are stable. In order to safely implement hydrate management strategies, it is required to understand mechanisms and processes connected to hydrate formation and accumulation in different multiphase systems involving gas, oil and water. A number of experiments have been performed using a visual rocking cell to measure and observe the various stages of hydrate formation, deposition and accumulation during continuous mixing and motion induced by the oscillation of the rocking cell to increase insight into the different processes leading to hydrate plug conditions. The experiments were performed in a gas-limited scenario considering the fluid combinations consisting of methaneethane gas mixture, water and mineral oil or condensate as hydrocarbon liquid. The effects of ii added monoethylene glycol (MEG) and a model anti-agglomerant (AA) were also studied in some of the experiments. Various stages of hydrate formation and accumulation were measured and observed under continuous mixing, as a function of several variables: temperature, pressure, presence of thermodynamic inhibitors and anti-agglomerants. Phenomena such as deposition, sloughing, hydrate particle growth, agglomeration and bedding were identified. In this work, a lower tendency of the hydrate to deposit on mineral oil wetted surfaces was observed, as compared to surfaces exposed to the condensate or the gas phase. Nevertheless, hydrate deposition was also observed in the oil system, mainly at surfaces only exposed to the gas phase. Hydrate formation in an experiment with mineral oil, 30% water cut and anti-agglomerant resulted in transportable hydrate slurry. Both the condensate and mineral oil tested were non-emulsifying, but shear-stabilized dispersion of the liquid phases was created prior to hydrate formation by mixing induced by the motion of the cell. The dispersion of the oil and water phases appeared to completely phase-separate during constant flow due to the incipient hydrate formation. A porosity analysis was performed based on analysis of visual appearance of hydrates in images captured from the video recordings of the experiments and calculated amount of hydrate phase in the system. Highly porous hydrate deposits formed in conditions with a large temperature gradient between the bulk and the surface, and high subcooling conditions, then suffering from sloughing due to the wetting and weight of the deposit and the shear of the fluids on the deposit. However, analysis of the experiments with fresh water demonstrated that sloughing was not detected in a narrow operational window defined by both subcooling lower than 4 °C and temperature gradient in the cell lower than 1 °C. The potential existence of an operational window for conditions without sloughing might be valuable for development of hydrate management strategies for blockage-free production. iii This thesis presents relationships between the phenomena observed (such as deposition, sloughing, glomeration, bedding) and parameters, such as subcooling, porosity and type of liquid hydrocarbon in the system. A revised conceptual model for hydrate formation and accumulation in non-emulsifying systems, which includes phase separation, agglomeration and deposition related mechanisms, has been developed based on the results from the experiments.